Early giant reveals faster evolution of large body size in ichthyosaurs than in cetaceans - Sander, P Martin; Griebeler, Eva Maria; Klein, Nicole; Juarbe, Jorge Velez; Wintrich, Tanja; Revell, Liam J; Schmitz, Lars (Science (American Association for the Advancement of Science), 2021)
Body sizes of marine amniotes span six orders of magnitude, yet the factors that governed the evolution of this diversity are largely unknown. High primary production of modern oceans is considered a prerequisite for the emergence of cetacean giants, but that condition cannot explain gigantism in Triassic ichthyosaurs. We describe the new giant ichthyosaur sp. nov. with a 2-meter-long skull from the Middle Triassic Fossil Hill Fauna of Nevada, USA, underscoring rapid size evolution despite the absence of many modern primary producers. Surprisingly, the Fossil Hill Fauna rivaled the composition of modern marine mammal faunas in terms of size range, and energy-flux models suggest that Middle Triassic marine food webs were able to support several large-bodied ichthyosaurs at high trophic levels, shortly after ichthyosaur origins.